Electrochemical performance of manganese-based composite electrode for supercapacitor application / Chan Pei Yi - Chan , Pei Yi (2017)
There were three manganese-based composite electrode systems being prepared in this work: (1) reduced graphite oxide-manganese oxide, (2) manganese-nickel oxide and (3) manganese oxide-poly (3, 4-ethylenedioxythiophene): poly (styrenesulfonate) (PEDOT: PSS). A two-electrode configuration of chronopotentiometry technique, with a constant current density of 2 mA cm-2 was applied for the preparation of composite electrodes. A stainless steel plate was acted as the substrate. The composite films deposited on stainless steel, or composite electrodes, were characterised by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and frequency response analysis (FRA). The changes in morphology, crystalline nature and electrochemical behaviours of the composite electrodes under the effect of deposition duration were investigated. In the first composite electrode system, the sheet-like reduced graphite oxide (RGO) was covered over the particles deposited on the substrate. It acted as a conductive pathway for electronic and ionic transportation. This composite electrode exhibited the highest specific capacitance when it was deposited at 13 mins. The continuous growth of particle with longer deposition duration led to the broken of RGO sheet, which subsequently affected the electrochemical performance. Second composite electrode system prepared, manganese-nickel oxide presented as a spongy-like structure under FESEM examination. There was no distinct boundary observed from FESEM images, indicating that two compositions had entangled well to each other. In this composite electrode system, 13 mins-deposited composite electrode obtained the best electrochemical performance. The manganese oxide-PEDOT: PSS as the third composite electrode system, was deposited in shorter duration (less than 1 min) compared with another two composite electrode systems due to the weaker adsorption on stainless steel. The morphology transformed from globular o more fibrous structure when the electrodeposition was carried out for longer duration. This improved the electronic and ionic transportation in the composite film. PEDOT: PSS enhanced the specific capacitance of manganese oxide by acting as conductive pathway for electron and ions. In this system, the composite electrode that was deposited at 40 s performed the best electrochemical performance.